Obstetric History and Risk of Short Cervix in Women with a Prior Preterm Birth - Frey, Heather A.; McLaughlin, Eric M.; Hade, Erinn M.; Finneran, Matthew M.; Rood, Kara M.; Shellhaas, Cynthia; Landon, Mark B. (American Journal of Perinatology, 2020)
Objective We aimed to assess the relationship between obstetric history and incidence of short cervical length (CL) at <24 weeks gestational age (GA) in women with a prior spontaneous preterm birth (PTB).Study Design Women with a singleton gestation and a history of spontaneous PTB on progesterone who received prenatal care at a single center from 2011 to 2016 were included. Those who did not undergo screening or had a history-indicated cerclage were excluded. The associations between short CL (<25 mm) before 24 weeks and obstetrical factors including: number of prior PTBs, history of term birth, and GA of earliest spontaneous PTB were estimated through modified Poisson regression, adjusting for confounding factors. Multiple pregnancies for the same woman were accounted for through robust sandwich standard error estimation.Results Among 773 pregnancies, 29% (n = 224) had a CL <25 mm before 24 weeks. The number of prior PTBs was not associated with short CL, but a prior full-term delivery conferred a lower risk of short CL (absolute risk reduction or aRR 0.79, 95% CI 0.63–1.00). Earliest GA of prior spontaneous PTB was associated with short CL. The strongest association was observed in women with a prior PTB at 160/7 to 236/7weeks (aRR 1.98, 95% CI: 1.46–2.70), compared with those with deliveries at 340/7 to 366/7 weeks. Yet, even women whose earliest PTB was 340/7 to 366/7 weeks remained at risk for a short CL, as 21% had a CL <25 mm. The number of prior PTBs did not modify the effect of GA of the earliest prior PTB (interaction test: p = 0.70).Conclusion GA of earliest spontaneous PTB, but not the number of prior PTBs, is associated with short CL. Nevertheless, women with a history of later PTBs remain at sufficiently high risk of having a short CL at <24 weeks gestation that we cannot recommend modifications to existing CL screening guidelines in this group of women.Key Points
Keywords: preterm birth; cervical length; short cervix; obstetric history